Mental health assessment of adolescent girls in an observational home in North coastal Andhra Pradesh: a cross sectional study - Kollabathula, Mounica; Bhimarasetty, Devi Madhavi (International Journal Of Community Medicine And Public Health, 2019)
Background: Adolescence is a stressful period involving changes both physically and mentally and requires support from family as well as peers. Assessment of mental health of adolescent girls in government special cum children home and observational home for girls in Visakhapatnam. Methods: It is a cross sectional descriptive study conducted in November 2016 using strengths and difficulties questionnaire among all 10 to 18 year old girls in the observational home. Social history was also taken additionally. Data was entered and analyzed in Microsoft Excel. Results: 16% girls had abnormal total difficulty scoring. Emotional problems were the highest (22%) followed by conduct (16%), peer problem (14%) and hyperactivity (5%). Abnormal pro social behavior was observed among 5% of the study population observed. Conclusions: Emotional problems were more common and only two thirds had and a normal total difficulties score. All children may be assessed periodically to know their psychological requirements and to identify at risk individuals.